Molecular and clinical profiles of T2DM, dyslipidemia, and periodontitis: insights into inflammatory and metabolic dysregulation - Peace Ngozi Okoro; Peace Ngozi Okoro; George Oche Ambrose; Victor Emmanuel Obaro; Chidiebere Valentine Ugwueze; Chidiebere Valentine Ugwueze; J. K. Olarinoye; Olalekan A. Agede (Frontiers in Endocrinology)
IntroductionType 2 Diabetes Mellitus (T2DM), dyslipidemia, and periodontitis are interconnected conditions that exacerbate systemic inflammation and metabolic dysregulation. Understanding the molecular and clinical profiles of these comorbidities is crucial for developing targeted interventions. This study investigates the molecular and clinical profiles of individuals with T2DM, dyslipidemia, and periodontitis to identify key markers and pathways underlying disease severity and progression.MethodsPeripheral blood mononuclear cells (PBMCs) were analyzed from five patient groups: T2DM poorly controlled with dyslipidemia and periodontitis (T2DMpoorly-DLP-H), T2DM well-controlled with dyslipidemia and periodontitis (T2DMwell-DLP-H), dyslipidemia and periodontitis (DL-P), periodontitis alone (P), and healthy controls (H). Correlations between molecular and clinical markers were assessed.ResultsThe T2DMpoorly-DLP-H group exhibited the most extensive molecular dysregulation, including unique upregulation of Plasminogen Activator, Tissue Type (PLAT) and consistent overexpression of Vanin-1 (VNN1), a key regulator of oxidative stress. HbA1c and fasting plasma glucose were highest in this group (HbA1c >12%, glucose >300 mg/dL), correlating strongly (R² = 0.88, p < 0.001). In contrast, the T2DMwell-DLP-H group demonstrated reduced gene dysregulation and improved glycemic control (HbA1c ~6.5%). Sex-specific differences were observed, with females exhibiting higher glycemic markers (p = 0.014) and males showing elevated lipid levels (p = 0.021).DiscussionThis study identifies Vanin-1 (VNN1) as a potential biomarker for systemic inflammation and highlights the role of Plasminogen Activator, Tissue Type (PLAT) in vascular dysfunction, emphasizing the critical importance of glycemic control in mitigating molecular and clinical dysregulation. These findings underscore the need for personalized, sex-specific strategies to manage these comorbidities effectively.